EARTHQUKES MECHANISMS AND STRESS FIELD IN THE SOLOTVYNO DEPRESSION OF THE EAST CARPATHIANS - Malytskyy, D.; Murovska, A.; Gintov, O.; Gnyp, A.; Obidina, O.; Mychak, S.; Grytsai, O.; Pavlova, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In the paper, two different methods are presented for evaluation of the stress field in the Solotvyno depression, the part of the Transcarpathians trough. In one method, stress field is determined by inverting the focal mechanisms of local earthquakes, in the other one – from data of field tectonophysics investigations. (In the Michael’s method, to determine principal stresses from source mechanisms it is needed to know which of the nodal planes exactly coinsides with the fault plane.) In the paper, a Vavrychuk’s version of Michael’s method and his fault instability constraint is used to identify the fault planes and the directions of principal stresses σ1, σ2, σ3 for 30 earthquakes which occurred in the area of Tyachiv during the period from 19.07.2015 to 06.08.2015. Focal mechanisms of the Tyachiv earthquakes are determined by graphic method, from polarities of first arrivals of P-waves, emergence angles (or incidence angles) at each of the stations and station azimuths. To determine principal axes of stress tensor from the data of tectonophysics investigations the cinematic approach is used for processing of tectonic slickensides with slide grooves and the structuralparagenetic method for processing of ruptures without the traces of displacement. In the paper, eight outcrops from the area of Solotvyno depression are analyzed: three of them are from the zone of Pienniny cliffs; three outcrops are located in the area of vulcanite formation in the Vyhorlat-Huta range, and two outcrops are from the Solotvyno depression itself. In all the outcrops, the types and orientations of recovered stress fields are found to recur. In general, stress fields of strike type and of faulting type prevail. The fields of faulting type are characterized by south-western orientation of tension axis σ3 and are similar to the mechanisms of Tyachiv earthquakes. Age correlation of the recovered stress fields is difficult to estimate only from field observations. That is why it is important to correlate the stress fields recovered in tectonophysics studies and from earthquake mechanisms. That enables to evaluate the current stress field.